OPTIMALISASI OPTIMALISASI MODEL MFT SEBAGAI ALAT UKUR KEBUGARAN GURU MGMP PJOK KOTA JAYAPURA - Tri Setyo Guntoro; Indra Yudistira (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
In the world of sports, it is important to have good physical fitness because good fitness can affect performance in various activities. Success in achieving anything productive often depends on a healthy and fit body. As a living being with a complete range of organs, keeping them functioning optimally is essential to ensure overall health. The Multi Fitness Test (MFT) is a form of test and measurement to measure a person's maximum oxygen capacity. The MFT test is very easy to do, using only a tape recorder (for the signal) and a field with a distance of 20 meters. The purpose of this PkM is to measure the cardiovascular fitness of MGMP PJOK Jayapura City teachers. The method used is two main activities, namely training and practical tests. The MFT results of the teacher service participants show that the fitness level of MGMP MPJOK Teachers in Jayapura city is in a category that is still in the very low category. The results of this unfavorable fitness level are the main task of sports teachers in order to increase fitness capacity for teachers and students in the future to have an excellent fitness level. This proposed PkM activity has two output targets, namely one article of PkM results published in the national journal Sinta 4 and one IPR from the Ministry of Law and Human Rights.